AP-1 Contributes to Chromatin Accessibility to Promote Sarcomere Disassembly and Cardiomyocyte Protrusion During Zebrafish Heart Regeneration. Issue 12 (5th June 2020) - Beisaw, Arica; Kuenne, Carsten; Guenther, Stefan; Dallmann, Julia; Wu, Chi-Chung; Bentsen, Mette; Looso, Mario; Stainier, Didier Y.R.
Abstract : Rationale: The adult human heart is an organ with low regenerative potential. Heart failure following acute myocardial infarction is a leading cause of death due to the inability of cardiomyocytes to proliferate and replenish lost cardiac muscle. While the zebrafish has emerged as a powerful model to study endogenous cardiac regeneration, the molecular mechanisms by which cardiomyocytes respond to damage by disassembling sarcomeres, proliferating, and repopulating the injured area remain unclear. Furthermore, we are far from understanding the regulation of the chromatin landscape and epigenetic barriers that must be overcome for cardiac regeneration to occur. Objective: To identify transcription factor regulators of the chromatin landscape, which promote cardiomyocyte regeneration in zebrafish, and investigate their function. Methods and Results: Using the Assay for Transposase-Accessible Chromatin coupled to high-throughput sequencing (ATAC-Seq), we first find that the regenerating cardiomyocyte chromatin accessibility landscape undergoes extensive changes following cryoinjury, and that activator protein-1 (AP-1) binding sites are the most highly enriched motifs in regions that gain accessibility during cardiac regeneration. Furthermore, using bioinformatic and gene expression analyses, we find that the AP-1 response in regenerating adult zebrafish cardiomyocytes is largely different from the response in adult mammalian cardiomyocytes. Using a cardiomyocyte-specific dominant negative approach, we show that blocking AP-1 function leads to defects in cardiomyocyte proliferation as well as decreased chromatin accessibility at the fbxl22 and ilk loci, which regulate sarcomere disassembly and cardiomyocyte protrusion into the injured area, respectively. We further show that overexpression of the AP-1 family members Junb and Fosl1 can promote changes in mammalian cardiomyocyte behavior in vitro. Conclusions: AP-1 transcription factors play an essential role in the cardiomyocyte response to injury by regulating chromatin accessibility changes, thereby allowing the activation of gene expression programs that promote cardiomyocyte dedifferentiation, proliferation, and protrusion into the injured area. Abstract : Supplemental Digital Content is available in the text.